How is Omicron different? - Thomson, Emma (Henry Stewart Talks, 2022)
Novel findings on the Omicron variant, Antigenic and biological properties of the Omicron variant, Immune escape and vaccine’s effectiveness, Clinical severity, Potential emergence of novel variants combining multiple mutations